Delayed Growth of Ferropericlase and Bridgmanite Controls Slab Residence at the 660‐km Discontinuity. Issue 6 (20th June 2021) - Chapman, Timothy; Clarke, Geoffrey L.
Abstract: Cold subducted oceanic lithosphere may stall in the uppermost portions of the lower mantle (660–700 km depth) as a consequence of its slow thermal equilibration and the negative d P /d T of reactions forming ferropericlase and bridgmanite. Evaluations of slab buoyancy in the lower parts of the transition zone have mostly neglected the effects of dynamic P–T paths and the temperature‐dependent expansion or contraction of stalled slabs. Forward predictions from mineral equilibria and thermal modeling posit slab residence at the base of the mantle transition zone for c . 150–160 Myr, dependent on geotherm and the depth of stagnation (between 660–700 km). Slab components can attain density thresholds following heating and phase transformations over distinct periods: Basaltic crust will become positively buoyant after c . 4 Myr whereas ultramafic components will become negatively buoyant after c . 150–160 Myr. Slab components may thus separate and independently transit or escape the transition zone under circumstances of equilibrated mineral assemblages. The 660 km seismic discontinuity presents a filter for the partial recycling of the upper oceanic lithosphere into the upper mantle. Key Points: Circa 150–160 Myr of slab heating required for a stagnant slab to become negatively buoyant The basaltic crust becomes buoyant after a short period of heating ( c . 4 Myr) at the 660‐km discontinuity The P‐T history of mineral equilibria are conducive to the 660‐km discontinuity filtering basaltic slab components